The Impact of Using Mobile Phones at SMP Negeri 11 Sarolangun Jambi - Juliansi, Niken Armanda; Fauzi, Taty; Surtiyoni, Endang (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The Impact of Mobile Phone Use in SMP Negeri 11 Sorolangun Jambi. Has a formulation and purpose, is: How the impact of Mobile Phone use on the learning behavior of grade VIII students at SMP Negeri 11 Sorolangun Jambi, and aims to describe the results of research on social behavior and student learning. The research method used is a qualitative descriptive analysis based on the philosophy of positivism with data collection techniques: observation, interviews, questionnaire surveys, and documentation and data analysis using Miles and Huberman techniques, consisting of: data reduction, data display, and conclusion drawing/verification". The results of the study explained that the use of mobile phones at SMP Negeri 11 Sarolangun Jambi school was the result of 20 respondents and 20 statements through a questionnaire survey with a percentage of 50% answering in agreement and 50% answering strongly agree. From the use of mobile phones to learning behavior in schools, teacher supervision is needed in using mobile phones only as a learning resource that is not found in textbooks or teaching materials, supervision from the Principal as a determinant of policies in using mobile phones at school and supervision of mobile phone use at home for parents by providing time limits on mobile phone use.